Alpha-estradiol and (R)-(−)-ibuprofen inhibit gastric cancer progression via GLI1 G-quadruplex - Li, Qiang; Pan, Pan; Xian, Qingqing; Li, Jingtan; Wang, Jingting; Cai, Jiaying; Wang, Jing; Jia, Yanfei; Sun, Haiji; Zhang, Lulu; Ma, Xiaoli (Frontiers in Pharmacology, 2025)
BackgroundThe transcription factor GLI1, aberrantly activated in gastric cancer, drives tumor progression, yet no approved inhibitors currently target this molecule. G-quadruplex (G4) motifs in promoter regions have emerged as promising therapeutic targets. This study explores G4 stabilization in the GLI1 promoter as a novel strategy to suppress gastric cancer progression.MethodsG4 formation in the GLI1 promoter was validated using circular dichroism. A dual-luciferase assay screened FDA-approved drugs for G4-stabilizing activity, identifying alpha-estradiol and (R)-(-)-ibuprofen as candidates. These compounds were evaluated for anti-tumor effects through in vitro assays (proliferation, migration, invasion) and in vivo xenograft models. Mechanistic insights into GLI1/PRKACB signaling were obtained via chromatin immunoprecipitation and pathway analysis.ResultsStable G4 structures were confirmed in the GLI1 promoter. Alpha-estradiol and (R)-(-)-ibuprofen suppressed GLI1 transcription and protein levels, significantly inhibiting gastric cancer cell proliferation, migration, invasion, and stemness. In vivo, both compounds reduced tumor growth and metastasis, with (R)-(-)-ibuprofen synergizing with cisplatin to enhance efficacy. Mechanistically, GLI1 directly regulated PRKACB expression, and G4 stabilization downregulated PRKACB, impairing epithelial-mesenchymal transition and cancer stemness.ConclusionTargeting GLI1 G4 structures with alpha-estradiol and (R)-(-)-ibuprofen effectively inhibits gastric cancer progression by blocking GLI1/PRKACB signaling. This study highlights G4-targeted therapy as a novel and clinically translatable strategy for gastric cancer treatment.